1995
DOI: 10.1038/bjc.1995.406
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and survival of lymphoid malignancy in the north-west of England: a population-based study

Abstract: Treatment and survival of lymphoid malignancy in the north-west of England: a population-based study JHAM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A number of published regional lymphoma review series have identified discrepancy rates of between 24% and 48% (Bird et al, 1984;Dick et al, 1987;Youngson et al, 1995). More recently, a comparative review of lymphomas submitted to a San Francisco community hospital identified a 11% discrepancy rate (Siebert et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of published regional lymphoma review series have identified discrepancy rates of between 24% and 48% (Bird et al, 1984;Dick et al, 1987;Youngson et al, 1995). More recently, a comparative review of lymphomas submitted to a San Francisco community hospital identified a 11% discrepancy rate (Siebert et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…When lymphoma pathology is reviewed by specialist haematopathologists, discrepancy rates of 24-48% between submitted and review diagnoses have been described (Bird et al, 1984;Dick et al, 1987;Youngson et al, 1995). A previous study by the AWLP identified a discrepancy rate of 20% in the 412 pathological specimens submitted for specialist review between January 1998 and January 2000 (Dojcinov & Attanoos, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 While encouraging responses are often obtained with current treatment modalities, lymphomas are still the sixth-mostcommon cause of cancer deaths in the United States, and diseases such as low-grade non-Hodgkin lymphomas (NHLs) and chronic lymphocytic leukemia (CLL) remain incurable at present. [12][13][14][15] Lymphomagenesis is often initiated and characterized by specific chromosomal rearrangements. These cytogenetic abnormalities, such as the t (8:14) and t(14:18) chromosome translocations, juxtapose oncogenes (c-myc and bcl-2 principally) to immunoglobulin enhancers and result in the deregulation of their expression.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of the various cell types present in the lymphoma serves as the basis for subclassification in follicle center lymphomas. It was shown however that, due to the subjective method of division (estimated per centage of cells and growth pattern), lymphomas are wrongly classified in 24% of cases [68], Inter-and intraob server differences of up to 50% were demonstrated when pathological slides were reviewed. Immunophenotyping by flow cytometry is considered useful and sometimes essential for accurate distinction from the other LGLPD (table 6).…”
Section: Pathology Immunophenotype and Cytogenetic Characteristicsmentioning
confidence: 99%